Science and speed addiction: the scholar's vocation in the age of efficiency. Issue 2 (1st January 2016) - Rider, Sharon
Abstract : This article examines the consequences of a set of unexamined assumptions related to instrumentalism as a fundamental presupposition in higher education and research policy. In particular, the idea of 'efficiency' as an ultimate value is contrasted with the idea of guiding principles with regard to the inner organisation of science, scholarship and teaching at the tertiary level. It is argued that the indispensable criterion for any sort of serious research or solid educational program is that the time required for thinking through a problem cannot be compromised without therewith compromising the very idea of science. At the same time, contemporary innovation and educational policy necessarily treat time as a cost to be reduced. Accommodation to external pressures to increase efficiency on the part of faculty, however, began already with the emergence of the modern European research university two centuries ago, as a response to market and bureaucratic exigencies. Thus, it is instructive to see how ideas such as that of faculty self-governance and the autonomy of science were deployed as a way of negotiating a path for the continued existence of the university under such conditions. The article concludes with a reflection on the future of the contemporary multiversity inspired by Kant's famous defence of the idea of a free faculty of 'pure' science.